IL-17A-Mediated Excessive Autophagy Aggravated Neuronal Ischemic Injuries via Src-PP2B-mTOR Pathway - Liu, Ting; Han, Song; Dai, Qingqing; Zheng, Jiayin; Liu, Cui; Li, Shujuan; Li, Junfa (Frontiers in Immunology, 2019)
We previously reported that astrocyte-derived proinflammatory cytokine interleukin (IL)-17A could aggravate neuronal ischemic injuries and strength autophagy both in oxygen-glucose deprivation (OGD)/reoxygenation (R)-treated neurons and peri-infarct region of mice with middle cerebral artery occlusion (MCAO)/reperfusion (R)-simulated ischemic stroke. In this study, the role and molecular mechanism of IL-17A in autophagy were further explored under ischemic condition. We found that exogenous addition of rmIL-17A remarkably (P<0.001) decreased cell viability, which companying with the increases of LC3 II accumulation (P<0.05 or 0.01) and Beclin 1 levels (P<0.05 or 0.001), and reduction of p62 levels (P<0.01 or 0.001) in OGD/R-treated N2a cells and cortical neurons (n=6). The levels of P-mTOR (P<0.001) and P-S6 (P<0.01) significantly decreased without the involvement of Akt, ERK1/2 and AMPK in cortical neurons under rmIL-17A and OGD/R treatments (n=6). Interestingly, the co-IP analysis exhibited that PP2B and mTOR could be reciprocally immunoprecipitated; and the addition of rmIL-17A increased their interactions, PP2B activities (P<0.001), P-Src (P<0.001) and P-PLCγ1 (P<0.01) levels in OGD/R-treated neurons (n=6 or 5). The PP2B inhibitor Cyclosporin A blocked the induction of excessive autophagy (P<0.05 or <0.001) and increased cell viability (P<0.001) after OGD/R and rmIL-17A treatments (n=6). In addition, the ICV injection of IL‐17A neutralizing mAb could attenuate autophagy levels (P<0.01 or 0.001, n=6) and improve neurological functions (P<0.01 or 0.001, n=10) of mice after 1 h MCAO/R 24 h or 7 d. These results suggested that IL-17A-mediated excessive autophagy aggravates neuronal ischemic injuries via Src-PP2B-mTOR pathway, and IL-17A neutralization may provide a potential therapeutic effect for ischemic stroke.